Discontinuous Demand Curves and Monopolistic Competition: A Special Case - Smith, Henry (Quarterly Journal of Economics, 1935)
Journal Article Discontinuous Demand Curves and Monopolistic Competition: A Special Case Get access Henry Smith Henry Smith Trinity College, Cambridge, England Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 49, Issue 3, May 1935, Pages 542–550, https://doi.org/10.2307/1883870 Published: 01 May 1935